2018
DOI: 10.1021/acs.jpcc.8b03914
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom and Side Chain Effects on the Optical and Photophysical Properties: Ultrafast and Nonlinear Spectroscopy of New Naphtho[1,2-b:5,6-b′]difuran Donor Polymers

Abstract: OpenBU http://open.bu.edu Chemistry BU Open Access Articles 2018-08-02 Heteroatom and side chain effects on the optical and photophysical properties: ultrafast and nonlin...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…Previous studies have observed the relationship between molecular planarity and two-photon absorption. 34,39,40 Here, the two-photon absorption cross section (d TPA ) is enhanced by over one order of magnitude for the planar bC (ca. 300 GM) relative to the twisted b compound (ca.…”
Section: Steady-state and Two-photon Absorption Measurementsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have observed the relationship between molecular planarity and two-photon absorption. 34,39,40 Here, the two-photon absorption cross section (d TPA ) is enhanced by over one order of magnitude for the planar bC (ca. 300 GM) relative to the twisted b compound (ca.…”
Section: Steady-state and Two-photon Absorption Measurementsmentioning
confidence: 96%
“…The extremely broad emission spectrum and the large Stokes shi suggest a drastic rearrangement of this exible molecule in the excited state. 33,34 Fig. 1 Normalized absorption and emission spectra of the trimers in chloroform.…”
Section: Steady-state and Two-photon Absorption Measurementsmentioning
confidence: 99%
“…The two-photon excited fluorescence technique 59,60 was used for the classical two-photon experiments. Our experimental setup has been described elsewhere 49,61 . In brief, the pure liquid (or a liquid solution of the compound of interest) contained in a 1 cm path length quartz cuvette is excited with the output beam of a Ti:Sapphire femtosecond pulsed laser (KMLabs, 800 nm, Δt ~30 fs) with a 80 MHz repetition rate.…”
Section: Methodsmentioning
confidence: 99%
“…synthesized a series of NDF‐based polymers PNDF9 – PNDF12 containing the identical conjugated framework and different π‐bridge. [ 292 ] PNDF9 and PNDF10 with the furan moiety in the backbone, displayed a broader absorption region and higher extinction coefficient those of PNDF11 and PNDF12 , which was favorable tendency of capturing more solar photons when used in a photovoltaic device. Besides, the polymers with the furan as π‐linker showed a higher two‐photon absorption cross sections relative to that of its thiophene counterparts owing to the planarity in the molecular backbone, suggesting the furan‐based compounds would possess higher charge transfer (CT) tendencies compared to the thiophene analogues.…”
Section: Naphthodifurans‐based Materials Used In Oscsmentioning
confidence: 99%